Psychological barriers to negotiation - Schneider, Andrea K. (Henry Stewart Talks, 2011)
Psychological barriers to negotiation, Endowment effect and its impact on negotiation, Loss Aversion and its impact on negotiation, Anchoring and its impact on negotiation, Overconfidence bias and its impact on negotiation, Zero-sum bias and its impact on negotiation, Reactive devaluation and its impact on negotiation
Reviewed at 2019/07/31